QAnon and Other Replacement Realities: How Religious Emotion Threatens Free Society but Can Also Contribute to a Progressive Future - Lundskow, George; MacMillen, Sarah (Lexington Books, 2023)
Q-Anon and Other Replacement Realities: How Religious Emotion Threatens Free Society but Can Also Contribute to a Progressive Future examines the historical and theological origins and the social-psychological effects of American conspiracy fantasies that Q-Anon and other right-wing beliefs foster. The authors argue that as progressive social change moves groups of people and the natural world from the margins to the mainstream, this inclusiveness “threat” mobilizes reactionary forces that embrace wild fantasies of Satanic sacrifice, Jewish global control, racial replacement, communism, cannibalism, pedophilia, orgies of rape and murder, and manipulations to steal elections and enslave the “normal” white population. To counter such gratifying myths and replace violence with mutually reinforcing social interaction the authors challenge the rhetoric that abuses power. The book maps out an alternative to destructive, hateful, polarizing, and conspiratorial discourse, with new more life-giving rational, emotional, and spiritual orientations. The authors hope this will move American society towards a new collective national identity, based on inclusiveness and equality, around a social character defined by compassion, gratitude, reverence, and love.